Welfare effects and gender dimensions of adoption of climate smart agriculture practices: Evidence from Kenyan small-scale farmers - Okumu, Boscow; Radeny, Maren A.O.; Cramer, Laura K. (Elsevier, 2025)
Agricultural production in Kenya is predominantly rain-fed and highly vulnerable to climate variability and change. Climate Smart Agriculture (CSA) is thus being promoted with the aim of increasing agricultural productivity, adapting to the changing climate, and reducing greenhouse gas emissions. Despite increased adoption of CSA practices by smallholder farmers, the heterogenous welfare effects are hardly understood as the results have been mixed. Moreover, despite the labour burden of rural women in agricultural production exceeding that of men– especially in Kenya–the drivers of adoption of CSA practices and the gender differential impact are barely understood. This study addresses these gaps by employing the probit model and the endogenous switching regression model to determine the drivers of adoption of CSA practices and the average and heterogenous welfare impact of adoption, including the gender differentiated impacts, using data from 1,809 smallholder farmers from diverse agroecological zones across 22 counties in Kenya. The results revealed that access to agricultural information, input subsidies, loans and credit and being a female headed household increases likelihood of adoption of CSA practices. Employment, access to off-farm income, higher household size and membership in local organizations reduces the likelihood of adoption of CSA practices. Further, the study revealed that adoption of CSA practices improves household welfare as measured by per capita monthly expenditure and savings, but the impact is significantly higher among female headed households compared to male headed households that adopted CSA practices. The study also found that non-adopters of CSA practices would be better off adopting CSA practices.